Paparan Pestisida melalui ASI: Implikasi terhadap Kesehatan Bayi dan Risiko Stunting - Imelda Iskandar; Azniah Syam; Mardiana Ahmad; Jumrah Sudirman; Armiyati Nur; Dinah Inrawati Agustin (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
The widespread use of chemical fertilizers and pesticides in modern agriculture has significantly increased crop yields. However, growing concerns about the potential health implications of these agricultural chemicals have prompted extensive research. This systematic review aims to investigate the extent to which exposure to these substances during pregnancy and breastfeeding can contaminate breast milk. We aim to assess the potential adverse effects of pesticide and fertilizer exposure in breast milk on infant health and development, focusing on contaminant prevalence, potential health risks, and the effectiveness of interventions to reduce exposure. This systematic review was conducted using the online databases PubMed, Scopus, and Google Scholar, covering the period from 2017 to 2024. Medical Subject Headings (MESH) and target keywords such as “Pesticides,” “Chemical Fertilizers,” “Breast Milk,” “Contamination,” “Maternal Health,” “Infant Health,” and “Stunting” were used in the search. All English-language publications were reviewed and included. This review included intervention studies such as randomized clinical trials and quasi-experimental studies. The search yielded 130 studies, and after screening, 10 studies were included in this review. The studies consistently showed pesticide exposure in breast milk, particularly in areas of intensive agriculture. A study in Latin America found that 100% of breast milk samples contained residues of dichlorodiphenyltrichloroethane (DDT). Research in Mexico reported that 76% of breast milk samples contained pesticide derivatives. A study in Saudi Arabia detected 16 types of organochlorine pesticides (OCPs). In Indonesia, all breast milk samples from female farmers contained p,p'-DDE residues above 0.001 mg/kg. All articles included in this review are observational studies, specifically cross-sectional and case-control studies, investigating the presence of pesticides and persistent organic pollutants (POPs) in breast milk. Various studies consistently show pesticide contamination in breast milk, raising serious concerns about its impact on infant health from an early age. Pesticide exposure through breast milk can have negative effects on growth and development, particularly on the nervous, endocrine, and reproductive systems. In Indonesia, pesticide exposure in agricultural environments has been identified as a significant risk factor for stunting in children. Keywords: Chemical Fertilizers; Pesticides; Breast Milk; Stunting